Effect of Fermentation Time on Acidity, Electrical Voltage and Volume of Apple (Malus domestica), Mango (Mangifera indica), Starfruit (Averrhoa bilimbi) Solutions - Yusfiani, Marnida; Ningsih, Liska Kustria; Azzahra, Nabila; Purba, Nesya Maharani; Arayan, Miftah; Sembiring, Rahel Natalia; Zubir, Moondra; Hakim, Abd (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
This study aims to analyze the effect of fermentation time on the electrical voltage, acidity (pH), and solution volume of apple, mango, and starfruit extracts as natural electrolytes in electrochemical cells. The fruit extracts were fermented using baker's yeast (Saccharomyces cerevisiae) for five days at room temperature, with measurements of electrical voltage, pH, and volume on days 1, 3, and 5. The results showed an increase in electrical voltage over fermentation time, with the highest value in starfruit (0.9 Volt, pH 2, final volume 140 mL). The decrease in pH and solution volume during fermentation indicated an increase in acidity and ion concentration which strengthened the conductivity of the solution as an electrolyte. This study proves the potential of local fruit extracts as a source of environmentally friendly electrolytes for alternative energy based on bioelectrochemistry.